Sublimation-assisted graphene transfer technique based on small polyaromatic hydrocarbons. (1st June 2017) - Chen, Mingguang; Stekovic, Dejan; Li, Wangxiang; Arkook, Bassim; Haddon, Robert C; Bekyarova, Elena
Abstract: Advances in the chemical vapor deposition (CVD) growth of graphene have made this material a very attractive candidate for a number of applications including transparent conductors, electronics, optoeletronics, biomedical devices and energy storage. The CVD method requires transfer of graphene on a desired substrate and this is most commonly accomplished with polymers. The removal of polymer carriers is achieved with organic solvents or thermal treatment which makes this approach inappropriate for application to plastic thin films such as polyethylene terephthalate substrates. An ultraclean graphene transfer method under mild conditions is highly desired. In this article, we report a naphthalene-assisted graphene transfer technique which provides a reliable route to residue-free transfer of graphene to both hard and flexible substrates. The quality of the transferred graphene was characterized with atomic force microscopy, scanning electron microscopy, and Raman spectroscopy. Field effect transistors, based on the naphthalene-transfered graphene, were fabricated and characterized. This work has the potential to broaden the applications of CVD graphene in fields where ultraclean graphene and mild graphene transfer conditions are required.